(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Yadav D, Adhikari A, Dhuingana B, Gurung H, Khatri N, Pandit S. 2022. In-vitro efficacy of Trichoderma isolates on Sclerotium rolfsii causing collar rot of chili. Asian J Agric 6: 97-102. The experiment was conducted in the Nepal polytechnic institute plant pathology laboratory to study the in-vitro efficacy of Trichoderma isolates on Sclerotium rolfsii Sacc. collar of chili, Bharatpur, Chitwan, Nepal by dual culture technique. The experiment was carried out in a completely randomized design (CRD) with four replications. The Trichoderma isolates, namely Kapilvastu isolate, Kavre isolates, Salyan isolates, Lalitpur isolates, and Taplejung isolates, were used in the experiment. The mycelium growth was measured at 2 DAI, 4 DAI, 6 DAI, 8 DAI, and 10 DAI. Also, the number of sclerotia, days to sclerotia, and width of the browning area at the interception region of interception were measured in 10 DAI. All the Trichoderma isolates significantly affect mycelium growth and the number of sclerotia formed. Among all the Trichoderma isolates, Kavre isolates show a good result with (74.44%) followed by Salyan isolates (74.22%) and Lalitpur isolates (73.55%) inhibition in the mycelium growth and several sclerotia (9.6 10) also formed. The lowest number of sclerotia was observed in Salyan isolates, which was three days, followed by Kapilvastu isolate, i.e., 20 days. The antagonist Kavre isolate can be used as a bio-control agent against S. rolfsii of chili in Nepal.